A simplified semi-empirical model for long-range low-frequency noise propagation in the turbulent atmosphere. (30th March 2023) - Zhang, Tianshu; Miller, Steven A.E.
Highlights: A modified long-range acoustic propagation solver is created. Wind tunnel tests are performed for validation. Example test cases presented for tornado and sonic boom propagation through a realistic atmosphere. Abstract: We present a semi-empirical long-range low-frequency acoustic propagation model, which accounts for atmospheric turbulence. Ostashev and Wilson's scattering model is combined with a ray-theory based refraction model to account for turbulent scattering and refraction via a turbulent absorption coefficient. The coefficient is ascertained via integration of scattered energy. The model is formulated, calibrated, and validated via corresponding experiments conducted within the National Science Foundation Boundary Layer Wind Tunnel. The predictions of the newly proposed 'bridging model' match the wind tunnel experimental data with an average error of 11.9%. Example predictions are shown to quantify the effect of turbulent kinetic energy and turbulent integral length scale on long-range infrasound propagation. To demonstrate the approach, we present predictions of the propagation of noise from a tornado and a nonlinear wave.